Strain penetration effect on cyclic response of corroded RC columns. (15th September 2021) - Cheng, Hu; Li, Hong-Nan; Biondini, Fabio; Wang, Dong-Sheng; Zou, Yun
Highlights: A modification method is proposed to predict the yield slip of corroded steel bars. FEMs of corroded RC columns are updated to simulate the anchorage slip deformation. Seismic behaviors of RC columns considering strain penetration effect are explored. Abstract: The anchorage slip of longitudinal reinforcement in the foundation (also called strain penetration effect) may affect the cyclic behavior of RC columns by inducing fixed-end rotations. This strain penetration effect could become more significant under reinforcement corrosion, which frequently occurs in RC structures exposed to the attack of aggressive agents such as chlorides. It is hence important to take corrosion effects into account in the modeling of strain penetration phenomena. This paper presents a modification of an existing stress versus slip hysteretic model for reinforcing steels to incorporate corrosion effects. Results of both pull-out tests of deformed steel bars and quasi-static tests of corroded RC columns are adopted for validation. Moreover, a parametric investigation is carried out to demonstrate the impact of structural parameters and corrosion levels on the cyclic response of corroded RC columns considering the strain penetration effect. The results highlight that the modified hysteretic model can efficiently simulate the anchorage slip. In addition, it is found that the strain penetration effect tends to be more significant for the RC columns with higher corrosion level, smaller aspect ratio, larger longitudinal reinforcement ratio, or lower axial load ratio.